Clinical Consequences of Delayed Corneal Ulcer Treatment: A Systematic Review - Syafridon, M Fadhil; Tanjung, Fadhilah Nisa; Yusuf (Asian Journal of Healthcare Analytics, 2026)
Corneal ulcer is an ophthalmic emergency that can lead to irreversible blindness if not treated promptly. Multiple studies have linked delayed management to an increased risk of severe complications such as corneal perforation, reduced visual acuity, and the need for keratoplasty. This study aims to assess the impact of delayed management of corneal ulcers on clinical outcomes and to identify factors contributing to treatment delays. This study is a systematic review of publications from 2020 to 2025, retrieved from the PubMed, Scopus, and ScienceDirect databases, using the keywords “infectious corneal ulcer,” “treatment delay,” and “visual outcome.” Eligible studies included observational designs (cohort, cross-sectional, retrospective) evaluating the association between delayed treatment (≥48-72 hours after symptom onset) and clinical outcomes. Three studies met the inclusion criteria following PRISMA 2020 screening guidelines. The analysis confirms that the interval between symptom onset and initiation of topical antibiotic therapy is a critical determinant of visual outcome. Early intervention guided by microbiological culture and resistance profiles markedly improves prognosis. Strengthening referral systems and adopting teleophthalmology services can effectively reduce diagnostic delays, particularly in resource-limited regions. Delayed management of corneal ulcers leads to severe clinical consequences affecting patients’ visual function. Public education, improved primary care capacity, and the application of rapid, technology-assisted referral systems are essential strategies to ensure timely diagnosis and prevent blindness-related complications.